2019
DOI: 10.1016/j.worlddev.2019.104635
|View full text |Cite
|
Sign up to set email alerts
|

The impact of blackouts on the performance of micro and small enterprises: Evidence from Indonesia

Abstract: Reliability of electricity supply is one of pressing challenges to many micro and small enterprises (MSEs) in developing countries. MSEs play a pivotal role in employment generation in these countries, but productivity of MSEs is relatively low. Little is known about how blackouts affect performance of MSEs. This paper is the first study to estimate the impact of power blackouts on productivity of manufacturing MSEs and to discuss the role of the government in addressing problem. We employ a pseudo-panel datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 41 publications
0
11
0
3
Order By: Relevance
“…However, the energy requirements for pretreatment by dewatering could be problematic for sustained operation in locations with frequent electricity blackouts. 76,77 For the treatment of sourceseparated excreta, the greater emptying requirements for the urine-diverting dry toilets and materials necessary for liquid treatment may not always be feasible, particularly in remote contexts. The characterization of these trade-offs helps navigate decision-making in the deployment of OP technology and highlight key areas of potential improvement in its sustainability.…”
Section: Elucidating Drivers For Cost and Emissionsmentioning
confidence: 99%
“…However, the energy requirements for pretreatment by dewatering could be problematic for sustained operation in locations with frequent electricity blackouts. 76,77 For the treatment of sourceseparated excreta, the greater emptying requirements for the urine-diverting dry toilets and materials necessary for liquid treatment may not always be feasible, particularly in remote contexts. The characterization of these trade-offs helps navigate decision-making in the deployment of OP technology and highlight key areas of potential improvement in its sustainability.…”
Section: Elucidating Drivers For Cost and Emissionsmentioning
confidence: 99%
“…The industrial sector, especially the micro and small enterprises (MSEs), with no backup emergency generators suffer from the low reliability of electrical supply during the peak-load periods. It was estimated that the total financial losses caused by electricity blackouts in the MES sector in Indonesia can reach nearly USD 5 million annually [17]. Although, the economic status is heavily influenced by the ESI, there is no official definition or indexing of the energy poverty in Indonesia, and the common consent is that the energy poverty can be avoided by providing electricity and clean energy to households.…”
Section: Energy Policy In Indonesia 21 Current Energymentioning
confidence: 99%
“…Several scholars have examined the economic consequences of electricity blackouts. They found that electricity blackouts are generally associated with adverse effects on labor productivity of affected firms due to work interruptions (Falentina and Resosudarmo, 2019;Fisher-Vanden et al, 2012;Anderson et al, 2007;Nkosi and Dikgang, 2018;Yamashita et al, 2008), making them particularly costly in economic terms with regard to welfare losses.…”
Section: Rq2: Was the Stock Market Able To Identify The Responsible Firm (Culprit)?mentioning
confidence: 99%